Multisystem Inflammatory Syndrome Associated With Severe Acute Respiratory Syndrome Coronavirus 2 in Children: A Case Series From Mayotte Island. (13th March 2021) - Cattaneo, Chiara; Drean, Maureen; Subiros, Marion; Combe, Patrice; Abasse, Soumeth; Chamouine, Abdourahim; Simon, Thomas
Abstract: During the COVID-19 outbreak in the French overseas department Mayotte, 11 children developed multisystem inflammatory syndrome (MIS-C). They all had a fever and gastrointestinal symptoms. Six patients were admitted to intensive care unit; management included intravenous immunoglobulin and corticosteroid. Severe acute respiratory syndrome coronavirus 2 was documented in all patients. The risk of developing MIS-C was much higher than in all of France.